BADAK JAWA SEBAGAI SUMBER INSPIRASI DALAM PENCIPTAAN SENI KRIYA LOGAM - M. Imam Khamdani (Corak : Jurnal Seni Kriya, 2015)
Creating an artwork with javan rhino as the source of inspiration was based on theauthor’s interest towards rhinoceros especially javan rhino. Javan rhino has its own uniquenesscompared to other species of rhinoceros and the phenomenon of its extinction that happenednowadays such as the skin’s physical form that is folded as if it’s forming an armor, its horn, andjavan rhino is considered as an animal that is almost extinct so the author was interested increating a metal craft artwork with Javan rhino as the theme in this final project as well as therequirement to graduate from bachelor degree of craft major.The methods of approach used are the expressive, contemplation, aesthetic, and thenthe data collection was done by using literature study and observation methods. The artworkscreated through three stages : exploration, design, and embodiment. Metal art presented in thisfinal project is a figurative artwork and the object was developed which is the result of Javanrhino embodiment.The produced artwork is a three-dimensional metal craft artwork with the shape ofJavan rhino as the inspiration of the craft art’s creation and has a shape development in such away. This artwork is expected to communicate with the society properly. This metal craftartwork was created neither for finding solutions nor solving the problems, but it is a touch ofexpression and a means of delivering a personal idea which is presented especially for art loversand generally for the society.Keywords: Javan rhino, Crafts art, Metal craft Menciptakan karya dengan sumber inspirasi Badak Jawa didasari atas ketertarikanpenulis terhadap binatang badak khususnya badak Jawa. Badak Jawa memiliki keunikantersendiri dari badak lainnya dan fenomena kepunahan yang terjadi saat ini seperti bentuk fisikkulit badak yang belipat seperti membentuk baju baja, cula, dan tergolong hewan yang hampirpunah sehingga penulis tertarik untuk menciptakan sebuah karya seni kriya logam bertemakanbadak Jawa ke dalam tugas akhir ini sekaligus sebagai syarat menyelesaikan studi S1 jurusankriyaMetode pendekatan yang digunakan adalah ekspresi, kontemplasi, estetis, kemudianmetode pengumpulan data dilakukan dengan studi pustaka dan observasi. Proses penciptaankarya seni ini memalui tiga tahapan yaitu, eksplorasi, perancangan, dan perwujudan. Karyalogam yang disajikan dalam Tugas Akhir ini merupakan karya figuratif dan dikembangkanobjeknya yang merupakan hasil dari perwujudan badak Jawa.Hasil karya ini adalah seni kriya logam tiga dimensi dengan bentuk badak Jawa sebagaiinspirasi dari penciptaan seni kriya dan memiliki pengembangan bentuk yang sedemikian rupa.Diharapkan karya ini dapat berkomunikasi dengan masyarakat secara baik. Karya seni kriya logam ini dibuat bukan dimaksudkan untuk mencari solusi ataupun menyelesaikan masalah,tetapi merupakan sebuah sentuhan ekspresi dan sarana penyampaian ide pribadi yangdisampaikan kepada penikmat seni pada khususnya dan masyarakat pada umumnya.Kata kunci: Badak Jawa, Seni kriya, Kriya logam